On the power of Literature.The works of Laura Alcoba and other artistic productions by children of militants in Argentina - Rosano, Susana (2022)
This article analyzes El azul de las abejas (2014), by Laura Alcoba, emphasizing its almost happy ending: a girl who, after having experienced a violent past in Argentina, exile and a laborious itinerary, manages to settle in another language, French, and thus build a new identity as a writer. In addition, the works produced by Alcoba dialogue with other artistic productions by children of militants in Argentina: Diario de una princesa montonera (Mariana Eva Pérez, 2012), Pequeños combatientes (Raquel Robles, 2013) and the photographic exhibition Arqueología de la ausencia (Lucila Quieto, 2011). This transmedial richness enables us to think about new articulations of meaning in relation to memory construction in the Southern Cone.